Development and Validation of RP-HPLC Method for the Estimation of Tenofovir and Emtricitabine in Bulk and Pharmaceutical Dosage Form - Sahoo, Biswa M.; Rao, Pallepogu Venkateswara; Rao, Naidu Srinivasa (Current Drug Research Reviews, 2024)
Background: A novel, simple, efficient, rapid, and precise reverse-phase highperformance liquid chromatography (RP-HPLC) method was developed for the estimation of Tenofovir and Emtricitabine in the bulk and pharmaceutical dosage form. The currently developed method was subsequently validated according to ICH guidelines in terms of linearity, accuracy, precision, the limit of detection, the limit of quantification, robustness, etc. Methods: The separation of the selected drugs was optimized after several trials including change of mobile phase and its composition, stationary phase, flow rate, column temperature, etc. The separation was performed by using an Inertsil ODS C18 column (250 mm x 4.6 mm, 5μ) and UV absorption was measured at 231 nm. Methanol: Acetonitrile: Water was selected as the mobile phase in the ratio of 50:20:30 (V/V/V) at a flow rate of 1 mL/min. As per International Conference on Harmonization (ICH) Q2 R1 guidelines, several validation parameters were evaluated which include specificity, linearity, precision, accuracy, the limit of detection (LOD), and the limit of quantitation (LOQ). Results: The acceptable degree of linearity range was found to be 40-100 μg/mL. The standard solution exhibited retention times of 3.06 minutes and 5.07 minutes for Tenofovir and Emtricitabine respectively. The LOD and LOQ obtained were 0.05 μg/ml and 0.02 μg/mL, 15 μg/mL, and 0.08 μg/mL for Tenofovir and Emtricitabine respectively. The percent recovery was found to be 98 to 102%. Conclusion: Hence, the proposed method is simple, selective, and specifically meets the requirements of ICH guidelines for the validation of the analytical method.
Keywords: validation